Smoking and Lung Cancer in Bangladesh - Uddin, Dayem; Mahmood, I; Kundu, S (TAJ: Journal of Teachers Association, 2009)
We studied the relationship between smoking and lung cancer risk in North-West and Southern region of our country with a very high baseline risk of lung cancer in male sex using data from a case-control study of lung cancer conducted between May, 1999 and May, 2004 at Rajshahi Medical College Hospital. Cases were 218 patients with incident, histologically confirmed lung cancer and controls were 436 patients admitted to the same hospital with non-neoplastic and non-lung diseases. Compared with never-smokers, the multivariate odds ratio (OR) for current smokers was 3.47[95%confidence interval (Cl) 2.31-5.20), and for ex-smokers 1.53 (95% Cl 0.81-2.87). Lung cancer risk increased by 20% (95% Cl 14% to 28%) for an increment of five cigarettes per day. The OR for smokers reporting occupational exposure to selected known or likely lung carcinogens was 7.22, compared with non-smokers without occupational exposure. This study further confirms that cigarette smoking is a strong determinant of lung cancer also in this high risk area of North-West and Southern area of our Bangladesh. TAJ 2009; 22(1): 207-211